Proceedings book of the Conference on Academic Success in Higher Education - Costa, Alexandra R. (2022)
(Excerpt of the Scientific Committee Chair message) The scientific program of the CASHE 2022 edition includes 12 presentations, which represents an acceptance ratio of 63% (i.e., a rejection rate of 37%). These contributions will be presented in 3 technical sessions. One of these sessions gathers the contributions which have been signaled as candidates for the best paper award, providing an opportunity for the jury to assess the presentations in parallel with the technical quality already evaluated by the reviewers. The conference program also includes one invited thematic session, two invited keynotes, and two roundtables, besides the traditional opening and closure sessions, the last one also including the delivery of the best paper award. The invited thematic session, organized by Leandro Almeida, from the Education Research Centre of the University of Minho, addresses the topic of “Improving success in Higher Education”. The invited keynotes will be delivered by Diana Mesquita, from the Portuguese Catholic University, and by Juarez Bento da Silva, from the Federal University of Santa Catarina, Brazil. Diana Mesquita addresses the topic “Do you feel students’ resistance to active learning? Possibilities to the teaching practice” and Juarez Bento Silva addresses the topic “Academic trajectory linked to research and extension: the experience of the Laboratory of Remote Experimentation of the Federal University of Santa Catarina”. The first roundtable will debate the contribution of Research Centers to the academic success of students who engage in R&D activities. The second roundtable will debate the impact of double degrees and internationalization in academic success, gathering Rectors from several Federal Institutes of Brazil, in a session moderated by Antonio Vega y de la Fuente, Vice-President of ISEP. To conclude, I would like to thank the entire Scientific Committee, and each member individually, for their contribution to the scientific quality of the event, translated into a careful review of the submissions received and the feedback given to the authors. Finally, I hope all CASHE2022 participants may enjoy the event to the fullest, interacting in it for the improvement of Academic Success in Higher Education.